Techniques Used to Translate the Subtitles of Humor in the Fresh Off the Boat Series - Adrianne Renata; Julia Eka Rini (Institute of Research and Community Outreach - Petra Christian University, 2024)
This study is about translation techniques used to translate the humor in the Fresh Off the Boat series subtitle from English to Indonesian. This study intends to determine the proper technique that can be used for every kind of humor yet preserve its funniness. The writer used Molina and Albir's (2002) theory of the eighteen-translation technique and Shade's (1996) theory for the types of humor. This study applied the qualitative method. The data that has been collected found only seven types of humor out of the twelve types of humor theory by Shade (1996). Additionally, from the eighteen techniques stated by Molina and Albir (2002), the translator only used six techniques to translate the types of humor in the Fresh Off the Boat series subtitles. The most suitable technique to translate humor is literal translation, while the most unsuitable technique is borrowing.